Juxtaposition of the T-cell receptor alpha-chain locus (14q11) and a region (14q32) of potential importance in leukemogenesis by a 14;14 translocation in a patient with T-cell chronic lymphocytic leukemia and ataxia-telangiectasia. - Davey, M P (1988)
We describe a t(14;14)(q11;q32) translocation in a patient with T-cell chronic lymphocytic leukemia and ataxia-telangiectasia (AT). By using a battery of joining (J)-segment probes from the T-cell receptor (TCR) alpha-chain locus TCRA, three distinct J alpha rearrangements were observed. One rearrangement reflected a normal TCRA variable (V) region V alpha-to-J alpha recombination. The second rearrangement was caused by the translocation even itself, which joined a DNA segment from 14q32 centromeric to the immunoglobulin heavy chain locus (IGH) and a J alpha gene located approximately 75 kilobases (kb) 5' of the TCRA constant region gene (C alpha). A third rearrangement involved a 17-kb internal deletion 3' to the translocation, a rearrangement within the J alpha locus that has been observed once before in a patient with AT. Analysis of these three rearrangements underscores the increase in aberrant locus-specific recombination in lymphocytes from patients with AT. Furthermore, these studies support the view that a growth-effecting gene is present in the 14q32 region that participates in the leukemogenic process.